دراسة منهج مادة تعليم اللغة العربية للصف الرابع في مدرسة الغزالي الإبتدائية الإسلامية المتكاملة ببالنكارايا - Mu’ammanah, Firda Aprillia (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Curriculum and learning are two important things in educational activities, and they both discuss what and how the educational process is carried out. This research aims to explain the curriculum for learning the Arabic language at Al-Ghazali Palangkaraya Integrated Islamic Primary School. As an integrated Islamic primary school, the curriculum implemented at Al-Ghazali School for learning Arabic is the 2013 curriculum from the Ministry of Religion for students. This research uses a qualitative approach with field research type. The data collection methods used are observation, interviews, and documents. The results of the research indicate that in the Al-Ghazali Integrated Islamic Primary School applies the 2013 curriculum from the Ministry of Religion to the students. The aim of learning Arabic at the Alghazali is to develop the ability to communicate in Arabic and to raise awareness that Arabic is a foreign language. The materials presented in teaching the Arabic language to the fourth grade are new phrases, reading, dialogue, structures, vocabulary, and exercises. The methods used by teachers are oral audio, singing, reading aloud, conversation, grammar and translation, lecture methods, and others. Meanwhile, the assessment used is a written test and an oral test. المنهج والتعلم هما شيئان مهمان في الأنشطة التعليمية، وكلاهما يناقش ماذا وكيف يتم تنفيذ العملية التعليمية. يهدف هذا البحث إلى شرح منهج تعلم اللغة العربية في مدرسة الغزالي بالانجكارايا الابتدائية الإسلامية المتكاملة. باعتبارها مدرسة ابتدائية إسلامية متكاملة، فإن المنهج المطبق في مدرسة الغزالي لتعلم اللغة العربية هو منهج 2013 من وزارة الدين للطلاب. يستخدم هذا البحث منهجًا نوعيًا مع نوع البحث الميداني. أساليب جمع البيانات المستخدمة هي الملاحظة والمقابلات والوثائق .أما نتائج البحث يدل أنه في مدرسة الغزالي، تطبق منهج 2013 من وزارة الدين على الطلاب. فإن الهدف من تعلم اللغة العربية في مدرسة الغزالي الإسلامية الابتدائية المتكاملة هو تنمية القدرة على التواصل باللغة العربية وزيادة الوعي بأن اللغة العربية لغة أجنبية.  فأما المواد المقدمة في تعليم اللغة العربية للصف الرابع هي عبارات الجديدة، والقراءة، والحوار، والتراكيب، والمفردات، والتدريبات. أما الطرق التي تستخدمها المعلمة فهي السمعية الشفوية، والغناء، والقراءة الجهرية، والمحادثة، والقواعد والترجمة، وطرق المحاضرة وغيرها. وفي الوقت نفسه، التقييم المستخدم هو اختبار الأسئلة المكتوبة واختبار الأسئلة الشفهية.